Assisting the Long-Term Unemployed: Results from a Randomized Trial - Robert Breunig; Deborah A. Cobb-Clark; Yvonne Dunlop; Marion Terrill (Institute for the Study of Labor (IZA), 2002)
Welfare reform in Australia centres on the concept of both economic and social participation. The policy concern is that people who fail to participate in economic and social life may become entrenched in disadvantage. In 2000 - 2001, a randomized trial was conducted by the Department of Family and Community Services in order to assess whether an intensive interview with successive follow-ups would result in increased economic and social participation for unemployed individuals who had been on income support for more than five years. We find evidence that participation in the trial led to a reduction in average weekly hours of work, but increased the amount of hours spent in study or training programs and the proportion of individuals engaged in such programs. We also find evidence of increased social integration associated with participation in the trial.
Keywords: J68; I38; H3; 330; active labor market programs; counseling and monitoring; long-term unemployment; propensity score matching; welfare reform; Langzeitarbeitslosigkeit; Sozialhilfeempfänger; Sozialpolitik; Berufliche Integration; Soziale Integration; Schätzung; Australien